Identification of Cetane Number in Solar Fuel from Pyrolysis of Plastic Waste - T Towijaya; K Anam; W D Lestari (Biomedical and Mechanical Engineering Journal (BIOMEJ), 2022)
The use of fuel is currently increasing, as well as the increasing number of plastic waste that comes from household and industrial waste. The need for processing plastic waste to reduce the volume of waste is very necessary. One type of plastic waste is the type of polypropylene. This type of polypropylene plastic waste is a type of waste that can be used as a basic material to produce alternative fuels in the types of diesel, gasoline, and kerosene. In this research work, a test will be carried out to determine the cetane number of this type of diesel fuel produced by the pyrolysis process, to the treatment of temperature and time variables so that a high cetane number is produced. Plastic waste processing uses pyrolysis and distillation methods to produce alternative fuels with processing temperatures of 190ºC, 200ºC, and 225ºC in 3 hours, 4 hours, and 5 hours. From testing the cetane number on the pyrolysis fuel, the cetane number from the process of making this alternative fuel itself reached the highest number, namely 64.1 at a processing time of 5 hours at a temperature of 200ºC.